Growth Differentiation Factor 11 Promotes Neurovascular Recovery After Stroke in Mice - Lu, Lu; Bai, Xiaofei; Cao, Yongliang; Luo, Haiyu; Yang, Xing; Kang, Lijing; Shi, Mei-Juan; Fan, Wenying; Zhao, Bing-Qiao (Frontiers in Cellular Neuroscience, 2018)
Background: Growth differentiation factor 11 (GDF11), a member of transforming growth factor-β (TGF-β) superfamily, was shown to rejuvenate cardiac and skeletal muscle function and to improve cerebral vasculature and neurogenesis in old mice. However, recent experimental data reported that raising GDF11 levels inhibited skeletal muscle regeneration and had no effect on cardiac hypertrophy. Our aim was to investigate the effects of GDF11 on brain repair during the recovery phase after stroke. Methods: Mice were subjected to distal middle cerebral artery occlusion, and recombinant GDF11 (rGDF11) was injected intraperitoneally once a day during days 7-13 after stroke. Neuronal precursor cells (NPCs) proliferation and angiogenesis were assayed at 14 days. Neuronal regeneration was assayed at 42 days. The beam-walking test and CatWalk were used to evaluate behavioral functions. Downstream pathways of GDF11 were also investigated. Results: GDF11 was upregulated in the ipsilateral peri-infarct cortex and subventricular zone at 14 days after stroke. Treatment with rGDF11 enhanced the number of newborn NPCs and endothelial cells, microvascular length and area, and brain capillary perfusion. Western blots showed that rGDF11 upregulated brain-derived neurotrophic factor (BDNF) and increased the levels of proangiogenic factor angiopoietin-2 (Ang-2) and phosphorylation of vascular endothelial growth factor receptor-2 (VEGFR-2). We also found that rGDF11 upregulated the transcription factors smad2 and smad3 phosphorylation, but these activations were blocked by a TGF-β receptor inhibitor SB431542. Moreover, rGDF11-induced angiogenic remodeling and NPCs proliferation were reversed by injection of SB431542, suggesting that GDF11 may exert its effect via the TGF-β/Smad2/3 signaling pathway. Finally, treating mice with rGDF11 resulted in a significant increase in neuronal regeneration and functional recovery. Conclusions: GDF11 promoted neurogenesis and angiogenesis and contributed to functional recovery after stroke in mice.